PERANCANGAN SISTEM INFORMASI PEMESANAN TIKET ONLINE WISATA CAMPING BERBASIS ANDROID DENGAN METODE AGILE - Muhtar Bahtiar; Bagas Setiyaki Wicaksono (CV. Multi Kreasi Media, 2023)
In the current era, the mechanism for the development of buying and selling products or services, especially in booking travel tickets online. advances in information and communication technology such as the internet and smartphones are very important to use, one of which is in ordering tickets online. However, apart from the superiority of technology that can be utilized, it's just that until now the Pasir Reungit Campground Tourism Object has several weaknesses, one of which is for the ticket ordering process, information on opening schedules and payment transactions are still done manually by directly coming to the tourist attraction. and cannot be arranged according to the schedule of visits by tourists who want to visit. As a solution to overcome this problem, the author conducted a study that aims to change the conventional system into a modern system by developing an Android-based e-ticket application. By taking advantage of currently available android devices, users can immediately see the tourist information they are going to, and directly buy travel tickets, so that time and energy efficiency occurs before going on vacation to the desired place. The travel ticket booking application is integrated with the database, making it easier for users to see real-time information, as well as what facilities will be obtained when buying the ticket. In its development, the author uses an agile approach so that the resulting application is in accordance with user needs. This application uses the Kotlin programming language, Android studio to develop the IDE concept of the application created and Firebase as a database to store data. The travel ticket booking application is integrated with the database, making it easier for users to see real-time information, as well as what facilities will be obtained when buying the ticket.